The stakeholder strategy : Profiting from collaborative business relationships - Svendsen, Ann, 1954- (San Francisco, CA : Berrett-Koehler Publishers, 1999)
In today's highly networked and competitive global economy, mounting social and environmental problems are forcing corporations to focus on more than just their stockholders' interest in meeting bottom line profitability. More and more companies are recognizing the value of identifying and building relationships with all of their organization's stakeholders-employees, customers, suppliers, and even communities. In fact, recent research has shown that companies that treat their employees well, create jobs in the local economy, develop innovative products and services, take care of the environme.
Preface; Acknowledgments; Chapter 1: Why Build Collaborative Stakeholder Relationships?; Chapter 2: Stakeholder Collaboration and the Bottom Line; Chapter 3: A Model for Corporate-Stakeholder Relations; Chapter 4: A Guide to FOSTERing Stakeholder Relationships; Chapter 5: Corporate Mission, Values, and Ethics-A Foundation for Relationship Building; Chapter 6: Aligning Corporate Systems and Structures; Chapter 7: Developing a Stakeholder Strategy; Chapter 8: Harnessing the Power of Long-Term Relationships; Chapter 9: Social Accounting-An Essential Management Tool.
Published for the Office of Older Adult Ministries, a Ministry of the General Assembly Council, Presbyterian Church (U.S.A.).
Includes bibliographical references (pages 189-196) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Business networks; Social responsibility of business; Social accounting; Réseaux d'affaires.; Entreprises -- Responsabilité sociale; Comptabilité sociétale.; BUSINESS & ECONOMICS -- Customer Relations; Business networks; Social accounting; Social responsibility of business; Stakeholder; Strategisches Management; Bedrijven; Sociale verantwoordelijkheid; Aandeelhouders; Festschriften; Festschriften